Optimalisasi Pengolahan Limbah Kaleng Menggunakan Mesin Press - Nidia Lestari (SIMETRIS, 2022)
Currently, many scrap collectors are still pressing used beverage cans manually, which hinders their productivity. This research aims to produce an effective tool in the form of a Press Machine with a crankshaft system, where this machine is made with the aim of optimizing waste treatment, especially beverage can waste. With this machine, the pressing of used beverage cans with a can size of 6.2 cm in diameter, 11.5 cm in height with a volume of 320 ml can be compacted into a smaller (flat) shape with a final height of 2 cm so that it can be said that the press machine has been increasing the efficiency of transport volume and storage area to wait for the next process.